Poetry as Embodied Language in Rilke. - Dowden, Stephen D. (MLN, 2026)
This essay explores Rilke's poetry as a way of making direct contact with the world "like the first human being." Situating Rilke within longstanding discussions on language from Plato and Aristotle to Humboldt, Merleau-Ponty, and Arendt, the essay argues that language is not merely an intellectual technology or arbitrary convention but a bodily, metamorphic capacity intrinsic to humans as a natural endowment. Poetry, in its rhythmic, metaphorical, and transformative qualities, restores the primal immediacy of speech as an embodied gesture, more like the spontaneities of dance than a matter of detached literary representation. Through close readings of various poems, the essay shows how Rilke resists the separation of subject from object, intellect from body, word from world. His metaphors do not objectify things as abstractions but enact reciprocal transformations, enabling moments of openness akin to what Keats calls negative capability and Canetti calls metamorphosis. Rilke's poetic practice thus unsettles the conventional objectification of language and affirms poetry as a primary modality of thinking—an attunement that makes possible renewed intimacy with the world, others, and the earth as a whole.